2009
DOI: 10.1103/physrevb.79.165428
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced disassembly of a graphene single crystal into a nanocrystalline network

Abstract: We report about investigations of time-dependent structural modifications in single-crystal graphene due to laser irradiation even at moderate power levels of 1 mW in a diffraction-limited spot. The modifications have been characterized by in situ scanning confocal Raman spectroscopy, atomic force height microscopy, and transport studies. The time evolution of the Raman spectrum reveals two different effects: on a short-time scale, dopants, initially present on the flake, are removed. The longer time scale beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
194
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 28 publications
10
194
4
Order By: Relevance
“…According to Krauss et al [11], these preliminary results indicate that additional defects are created when focusing the laser down to a micrometer-sized spot. It seems, in addition, that the application of the Raman technique to CVD graphene (instead of exfoliated), is harmful to the sample, despite the employment of lower power (64 kW/cm 2 against [11] 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 400 kW/cm 2 ) and energy (3.8 MJ/cm 2 against [11] 12 MJ/cm 2 ) densities. Actually, Tiberj et al [10] reported about photo-induced doping as directly connected to the substrate preparation, evidencing that, when graphene is transferred onto Si/SiO2 substrates used as-received and without any cleaning, the doping of graphene flakes remains constant for all the entire laser power range.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…According to Krauss et al [11], these preliminary results indicate that additional defects are created when focusing the laser down to a micrometer-sized spot. It seems, in addition, that the application of the Raman technique to CVD graphene (instead of exfoliated), is harmful to the sample, despite the employment of lower power (64 kW/cm 2 against [11] 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 400 kW/cm 2 ) and energy (3.8 MJ/cm 2 against [11] 12 MJ/cm 2 ) densities. Actually, Tiberj et al [10] reported about photo-induced doping as directly connected to the substrate preparation, evidencing that, when graphene is transferred onto Si/SiO2 substrates used as-received and without any cleaning, the doping of graphene flakes remains constant for all the entire laser power range.…”
Section: Resultsmentioning
confidence: 89%
“…1a shows the Raman spectrum of the CVD graphene, collected in macro-configuration with a laser (=532 nm, wavelength) spot of d=100 μm diameter and a laser power at the sample P=11.7 mW (power density, Ψ150 W/cm 2 ) for Tinteg=60 s integration time. The spectrum is compared with a typical one from micro-Raman of exfoliated graphene [11], to highlight the similar quality, apart from the slightly higher D peak in the CVD case. Considering the spatial averaging character of the macrotool, this encouraging result suggested us to perform micro-Raman investigation to select the best areas, which reasonably should show an even better quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The G band is characteristic of sp2-hybridized C = C bonds in graphene sheets (Childres et al, 2013); whereas, the D band is associated with structural defects and partially disordered structures of the sp2 domain (Childres et al, 2013). The 2D band located at 2718 cm −1 originates from a double-resonance process (Krauss et al, 2009;Yan et al, 2011). The calculated values of I D /I G listed in Table 1.…”
Section: Characterization Of Po-gr and Po-gr/pedot:pss Filmmentioning
confidence: 99%